For a comprehensive analysis of grooves and indentations for the level (500), fines per bar, of rainfall in Iraq for the period (2007-2018) (Journal of the College of Basic Education, 2022)
The research showed the comprehensive analysis of the grooves and dentations through the analysis of the synoptic weather maps for the level of 500 (millibars) for the observation ((GMT1200 diurnal for eleven years) starting from 2007-2018)) and four climatic stations (Mosul, Rutbah, Baghdad, Basra) representing the sections of the surface were chosen The study area (north, east, west, south) The research showed the climate variation in the study area in time and place in the amount of rain, as the gullies recorded the highest average number of days of stay and the intensity of rain in Mosul station , As for the lowest average number of days of stay and rain, the Basra station recorded during the rainy season due to the low temperatures and the retreat of the subtropical high pressure systems and their rush towards the south away from the study area, which allows the progress and increase of the gullies movement, and the relationship between the gullies and the amount of rain for all stations showed a positively positive correlation. , As for the dents, the lowest rate of furrows for the number of days of stay and the total rainfall for all stations during the rainy season due to the decrease of the subtropical high pressure towards the south, and the statistical relationship between the dents and the amount of rain showed an inverse correlation as it decreased with increasing frequency and increasing with decreasing frequency.